Pengaruh Kadar Minyak Kelapa Terhadap Morfologi Sifat Thermoset Rubber Dengan Filler Abu Sawit - Carbon Black - Afrila Afrila; Bahruddin Bahruddin; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Plasticizer and filler have important role to making thermoset rubber. The function of plasticizer is to assist spreading process of filler in rubber and to improve elasticity of thermoset rubber. Meanwhile function of filler is to increase mechanical properties of thermoset rubber. The purpose of this study is to obtain the best conditions of the vulcanization process in the manufacture of thermoset rubber with coconut oil as plasticizer and fly ash/carbon black as filler hybrid, whichis the variation of cococnut oil content are 2,5 phr, 5 phr and 7,5 phr and filler hybrid FA/CB content are 30 and 50 phr with ratio 100/0 , 50/50 and 30/70. The results of thermoset rubber will be tested, it’s mecanical properties such as tensile strength, elongation at break, tension set, abrasion, hardness, and water absorption also thermoset rubber morphology. Based on average yield mecanical properties and morphology tested is obtained that the best conditions vulcanizationprocess is thermoset rubber with coconut oil content 5 phr and filler hybrid content of 30 phr with ratio FA/CB of 30/70. The best mechanical properties was given on tensile strength 24,8 MPa, elongation at break 816 %, tension set 2,17%, hardness 54±5 shore A, abrasion resistance 0,14 mm3/kg and also for water absorption 0,59%Keyword : Carbon Black, Fly Ash, Filler, Plasticizer, Thermoset Rubber, Vulcanization